“Махтумқулинома”- юксак идрок ва тафаккур маҳсули (SCIENCE and SOCIETY, 2019)
In the article deals with the interpreters the poem “Mahtumkulinoma” in the Uzbek language. In the article the translators’ skill in using words in the process of translating the verses of Makhtumquli are analyzed; the value of a word in the literary-artistic translation is discussed.